More than economic crisis - Brychtová, Šárka (Univerzita Pardubice, 2010)
The present article aims to provide an uneconomic view of the current economic crisis. The text deals with the substance of the crisis in its wide connections and creates a parallel between a general crisis and the economic crisis. It perceives the economic crisis like a kind of illness and indicates a possible solution in the future. The article also contains a hidden philosophical meaning.
Keywords: economic crisis; crisis like an illness; causes of crisis; way out of the crisis; balance